Excessive overshooting of cumulonimbus - MUKHERJEE, A. K.; CHAUDHIURY, A. K. (MAUSAM, 1979)
It is generally accepted that the classical parcel method gives the correct estimate of the height of cumulonimbus clouds. Formerly it was thought that parcel of air rising convcctively could rise from convective condensational level upto a level where the temperatures or the parcel and the environment become equal. We may call it as equilibrium level orZe . Between CCL and Ze the parcel rise since the temperature of the parcel is higher and the density is always lower than the environrnent• This Ze is also the anvil level. It has been found that the cumulonimbus often cresses the anvil level and grows higher. This phenomenon is termed as overshooting. Based on this classical parcel method theories for overshooting have been proposed by Newlon (1966) and Rocha (1967).They postulated that the rising parcel would cross Ze because of the inertia and ould go to a level Zp so that the energy acquired by the parcel during its journey from CCL to Ze is spent up. On some occasions it has been round that heights or cumulonimbus have exceeded Ze. This paper deals with such cases.This phenomenon has been termed as excessive overshooting. Fujita (1974) presented a modelof overshooting cumulonimbus. With the help or this and the model presented by Roach a mechanism of cooling of the immediate environment of the overshooting clouds have been proposed. This modified environment then allows further growth of the cloud . Based on the mixing of cold air due to over shooting surrounding air in proportion to their speeds, a quantitative estimation of the cooling of the environment has been ppossible. From the considerations of inertia again it has been proposed that the rising parcel can go beyond Zp and 10 h eight Zp' which can be easily calculated from thermodynamic diagrams. The calculald values ha ve bam compared with observed heights or excessive overshooting and the agreements have been quite good.